POLYCULTURAL GROWTH IMPROVEMENT PERFORMANCE OF CATFISH (Clarias sp.) AND TILAPIA FISH (Oreocromis niloticus) CULTIVATED IN THE BIOFLOCK CULTIVATION SYSTEM - Sudirman, Andik; Rahardjo, Sinung; Rukmono, Djumbuh; Harryes, Regil Kentaurus; Alamsah, Safingi (Politeknik Kelautan dan Perikanan Dumai, 2023)
The biofloc system is a solution for intensive cultivation activities. This is because in biofloc system the are heterotrophic bacteria that can reuse waste from cultured organisms so as to improve water quality. However, the biofloc system can cause high nitrite production if the dissolved oxygen concentration in the water is below the optimum value. High nitrite concentrations can cause brown nitrite, causing fish to suffocate even though the oxygen concentration in the water is sufficient. Polyculture can be a solution to reduce the concentration of biofloc so that brown nitrite can be prevented. Therefore, a research was conducted with the aim of knowing the effect of the composition of the best polyculture biota in order to produce high cultivation performance. The ratio of tilapia and catfish used included 80% catfish and 20% tilapia fish (treatment A), 70% catfish and 30% tilapia fish (treatment B), 60% catfish and 40% tilapia ( treatment C), and 100% catfish (treatment D). Maintenance is carried out for 60 days where feeding is done on a restricted basis. The results of the research carried out showed that the best FCR, ADG and SR were in treatment C with consecutive values of 1.27 ± 0.02 (FCR), 1.4 g/day (ADG) on the last maintenance day, 95.11 ± 1.02% (SR). This study shows that the performance of cultivation in biofloc systems in polyculture is better than monoculture.